Resilience of Grain Storage Markets to Upheaval in Futures Markets - Hayhurst, Emma; Brorsen, B. Wade (Research on World Agricultural Economy, 2023)
The past two decades have had times when grain cash and futures markets did not converge during delivery. What was the economic impact of this non-convergence on storage markets? To answer this question the supply of storage is estimated for corn, soybeans, and wheat. The lack of convergence is measured using a historical basis. The econometric model shows no relationship between the supply of storage and the lack of convergence. Thus, empirical results suggest that markets were able to adapt to the lack of convergence. Overall, the research indicates the resilience of storage markets to structural change. ER